Development of seed cube technology for successful afforestation through direct seeding of Thespesia populnea trees - Jawahar, R. (2022)
Seed balls are gaining popularity as a means to improve tree cover and facilitate ecological restoration. Currently, seed balls are prepared without properly addressing seed dormancy, seed germination percentage and seed vigour. Implementation of latest seed enhancement technologies such as seed coating and seed priming can facilitate germination of tree seed balls. Flat seed cubes have an advantage over spherical shaped seed balls in aiding seed germination and rooting of new germinants. A series of experiments were conducted using Thespesia populnea seeds to standardise seed coating technique, humid priming technique and cube media composition. The results revealed that seeds of T. populnea coated with 4 g kg-¹ Shidocoat (a gibberellic acid-based seed coating formulation developed by Tamil Nadu Agricultural University and marketed by Vriksha Agro Ventures, India) followed by humid priming (24 hours soaking + 3 days humid incubation) and embedded in cube media (700 g soil, 130 g sawdust, 80 g bone meal, 40 g vermicompost and 50 g arbuscular mycorrhizal fungi) recorded an increase of 46.0% germination, 180.8% speed of emergence on the 21st day, 7.5% root length, 23.5% shoot length, 14.1% total seedling length, 23.1% dry matter production and 225.3% vigour index over the soil cube media. Owing to its significantly superior performance, it is recommended that the improved seed cubes of T. populnea be directly placed on the surface of soil in chosen areas, so that they can germinate when they receive the desired moisture through rainfall or irrigation.